Hepatic glucose metabolic responses to digestible dietary carbohydrates in two isogenic lines of rainbow trout - Song, Xuerong (Biol Open, 2018)
Rainbow trout (Oncorhynchus mykiss) was recognized as a typical ‘glucose-intolerant’ fish and poor dietary carbohydrate user. Our first objective was to test the effect of dietary carbohydrates themselves (without modification of dietary protein intake) on hepatic glucose gene expression (taking into account the paralogs). The second aim was to research if two isogenic trout lines had different responses to carbohydrate intake, showing one with a better use dietary carbohydrates. Thus, we used two isogenic lines of rainbow trout (named A32h and AB1h) fed with either a high carbohydrate diet or a low carbohydrate diet for 12 weeks. We analysed the zootechnical parameters, the plasma metabolites, the hepatic glucose metabolism at the molecular level and the hormonal-nutrient sensing pathway. Globally, dietary carbohydrate intake was associated with hyperglycaemia and down regulation of the energy sensor Ampk, but also with atypical regulation of glycolysis and gluconeogenesis in the liver. Indeed, the first steps of glycolysis and gluconeogenesis catalysed by the glucokinase and the phospenolpyruvate carboxykinase are regulated at the molecular level by dietary carbohydrates as expected (i.e. induction of the glycolytic gck and repression of the gluconeogenic pck); by contrast, and surprisingly, for two other key glycolytic enzymes (phosphofructokinase enzyme – pfkl and pyruvate kinase – pk) some of the paralogs (pfklb and pklr) are inhibited by carbohydrates whereas some of the genes coding gluconeogenic enzymes (the glucose-6-phosphatase enzyme g6pcb1b and g6pcb2a gene and the fructose1-6 biphosphatase paralog fbp1a) are induced. On the other hand, some differences for the zootechnical parameters and metabolic genes were also found between the two isogenic lines, confirming the existence of genetic polymorphisms for nutritional regulation of intermediary metabolism in rainbow trout. In conclusion, our study determines some new and unexpected molecular regulations of the glucose metabolism in rainbow trout which may partly lead to the poor utilization of dietary carbohydrates and it underlines the existence of differences in molecular regulation of glucose metabolism between two isogenic lines which provides arguments for future selection of rainbow trout.